Experimental study on mixing phenomenon inside reactor down-comer under single-loop injection using laser induced fluorescence. (November 2019) - Zhang, Qi; Su, Jianke; Du, Weian; Yuan, Hongsheng; Yang, Fan; Tan, Sichao
Abstract: The boron dilution transient may cause re-criticality during an emergency shutdown, and the mixing between de-borated slug and boric acid inside the annular down-comer and the lower plenum is the inherent mechanism against such accident. A visualization pressure vessel model was built to study the mixing phenomenon and analyze the mixing mechanism, the injection coolant with boric acid is represented by dye-sucrose solution, and the dye concentration distribution at longitudinal section and different cross sections was obtained by LIF. In the slug mixing test, the entrance dye solution spread along the azimuthal direction and stagnant area was detected. For the emergency core cooling injection with density difference, the tracer transportation of momentum dominant and buoyancy driven flow differs a lot. The former leads reverse flow from the lower plenum towards the top of down-comer. For the latter situation, the stratification of tracer in vertical direction is formed by gravity effect. When there exists density difference, the segmentation of the injection and the ambient fluid is inevitable, which is not favorable for evenly distribution in the whole RPV structure. Highlights: Fluid mixing phenomenon inside the reactor down-comer was observed by non-contact measurement, the two-dimension horizontal and vertical concentration fields were obtained. With single inlet, the stagnant area beyond the entrance was confirmed, and it was analyzed by entrance Reynolds number. The mixing mechanism of momentum and buoyancy-effect were quantitatively compared and analyzed.